Pemanfaatan media pembelajaran konvensional dalam mengembangkan motivasi belajar siswa kelas 3 ICP di MINU Tratee Putera Gresik - Mahsunah, Nafsiyatul (Maliki Interdisciplinary Journal, 2024)
Motivation to study is an important factor that influences student learning outcomes. To increase enthusiasm for learning in students, the use of conventional learning media can be an effective strategy. This research aims to understand how the use of conventional learning media can increase the enthusiasm for learning of grade 3 ICP students at MINU Tratee Putera Gresik. The research method used was an experiment with a pretest-posttest group design. The research results show that the use of conventional learning media can increase students’ interest in learning, especially in terms of interest and desire to learn. These results indicate that the use of conventional learning media can be an effective strategy in increasing students’ learning motivation. Thus, this research contributes a lot to the development of more effective teaching strategies and increases the quality of education.